Revolutionizing Islamic Education: The Primary Role of Teachers in Society 5.0 Learning Process - Wantini Wantini; Reni Sasmita; Oqy Andaresta; Yuike Silvira; Rika Wulandari; Septiani Azzahra (AL-ISHLAH: Jurnal Pendidikan, 2023)
Education has various responsibilities and challenges in the age of 5.0. Changing attitudes and behaviors in children who belong to the alpha generation and are accustomed to the rapid advancement of technology and information is one of the issues facing educators. The attitudes that emerge include addiction to technology, cyberbullying, and even the erosion of values. Islamic Religious Education teachers are essential to the education that takes place in the 5.0 age group because they play a crucial role in enhancing students' morals and ethics. The research technique utilized in this study is called library research, and its data sources are books, scholarly articles, and documents pertinent to the study's problem. Solving challenges and thinking critically and creatively are necessary abilities in the 5.0 era of society because they will enable people to benefit from developments in the 4.0 era of industry. The function of PAI teachers in the educational process in the period of Society 5.0 requires that they be imaginative and creative in the learning process, as well as qualified and technologically literate. The role of teachers of Islamic religious education in the period of Society 5.0 in relation to students can enable students to engage in creativity and innovation in learning, making them capable of thinking critically and solving issues and able to develop their morals and character.